Parallel Paths to Resilience: Why Self-Control Fails to Moderate the Impact of TikTok on Student Coping Stress - Anggraini, Dina Amalia; Radiani, Widiya Aris; Musfichin (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: Social media has transitioned from a communication tool to a primary instrument for emotion regulation among university students. While TikTok is increasingly used for stress relief, the role of self-control in "governing" this relationship remains poorly understood. This study utilizes Moderated Regression Analysis (MRA) to examine how self-control moderates the link between TikTok intensity and coping stress among 402 undergraduates. Our findings reveal that TikTok intensity is a significant driver of coping stress (R2 = .268), validating its role as an effective emotion-focused coping mechanism. Crucially, however, self-control did not function as a moderator (p = .424); instead, it emerged as a powerful, independent predictor of resilience. This suggests a "decoupling" of digital behavior and internal psychological traits: TikTok provides immediate emotional relief, while self-control fosters long-term psychological endurance through separate cognitive pathways. These results challenge the prevailing narrative that self-control is merely a "gatekeeper" for digital consumption and advocate for university mental health programs to treat digital literacy and self-regulation training as distinct, parallel interventions  Keywords: TikTok, Coping Stress, Self Control